2018
DOI: 10.1186/s12868-018-0401-8
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles for microRNA in the regulation of Drosophila circadian clock

Abstract: BackgroundThe circadian clock, which operates within an approximately 24-h period, is closely linked to the survival and fitness of almost all living organisms. The circadian clock is generated through a negative transcription-translation feedback loop. microRNAs (miRNAs) are small non-coding RNAs comprised of approximately 22 nucleotides that post-transcriptionally regulate target mRNA by either inducing mRNA degradation or inhibiting translation.ResultsIn recent years, miRNAs have been found to play importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 67 publications
1
55
0
Order By: Relevance
“…Post-transcriptional regulation by miRNA has been implicated in a broad range of processes, including the circadian system (Xue & Zhang 2018). Recent studies in plants revealed that miRNAs are also involved in the photoperiodic timing of flowering (Jung et al 2007;L.…”
Section: Introductionmentioning
confidence: 99%
“…Post-transcriptional regulation by miRNA has been implicated in a broad range of processes, including the circadian system (Xue & Zhang 2018). Recent studies in plants revealed that miRNAs are also involved in the photoperiodic timing of flowering (Jung et al 2007;L.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging roles of miRNA in the control of different aspects of circadian rhythms have been recently uncovered [33]. Here, we screen Drosophila miRNA mutants and demonstrate that miR-210 is critical for circadian locomotor rhythms.…”
Section: Discussionmentioning
confidence: 98%
“…miRNAs are small non-coding RNAs, which repress target gene expression through mRNA degradation and/or translation inhibition, thus play crucial roles in posttranscriptional regulation [31]. Recent studies have uncovered functions of the miRNA biogenesis pathway and specific miRNAs in the regulation of different aspects of animal circadian rhythms [30,[32][33][34]. For instance, mouse miR-132/212 modulates the seasonal adaptation and circadian entrainment to day length [35].…”
mentioning
confidence: 99%
“…The significance of post-transcriptional regulation in circadian rhythms has been demonstrated by monitoring the core clock gene expression 15, 52 and screening miRNAs involved in rhythmic behavior 44, 4749, 5358 . However, elucidation of the underlying molecular mechanism is impeded because only a few of the predicted miRNA-mRNA interactions have been verified.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the miRNA biogenesis pathway considerably weakens the rhythm in locomotor activity 26 . Although the rhythmically expressed miRNAs have been identified 2729 , only a limited set of miRNA-target pairs have been verified to affect circadian rhythms 26, 3033 . Decoding of the miRNA-mRNA interaction network is difficult because of incomplete complementary pairing between miRNAs and targets as well as context-dependent dynamics of the miRNA-target interactions.…”
Section: Introductionmentioning
confidence: 99%